![log_{2}^{2}(x-1)+log_{2}(x-1)<2 log_{2}^{2}(x-1)+log_{2}(x-1)<2](https://tex.z-dn.net/?f=log_%7B2%7D%5E%7B2%7D%28x-1%29%2Blog_%7B2%7D%28x-1%29%3C2)
ОДЗ : x - 1 > 0 ⇒ x > 1
Сделаем замену :
![log_{2}(x-1)=m\\\\m^{2}+m-2<0\\\\(m+2)(m-1)<0 log_{2}(x-1)=m\\\\m^{2}+m-2<0\\\\(m+2)(m-1)<0](https://tex.z-dn.net/?f=log_%7B2%7D%28x-1%29%3Dm%5C%5C%5C%5Cm%5E%7B2%7D%2Bm-2%3C0%5C%5C%5C%5C%28m%2B2%29%28m-1%29%3C0)
+ - +
_________₀____________₀___________
- 2 1
/////////////////////////
-2\\\\x-1>0,25\\\\x>1,25\\\\log_{2}(x-1)<1\\\\x-1<2\\\\x<3" alt="log_{2}(x-1)>-2\\\\x-1>0,25\\\\x>1,25\\\\log_{2}(x-1)<1\\\\x-1<2\\\\x<3" align="absmiddle" class="latex-formula">
Ответ : x ∈ (1,25 ; 3)
6+log_{\frac{1}{2} }(3x+1)" alt="2)log_{\frac{1}{2} }^{2} (3x+1)>6+log_{\frac{1}{2} }(3x+1)" align="absmiddle" class="latex-formula">
ОДЗ : 3x + 1 > 0 ⇒ x > - 1/3
Сделаем замену :
0\\\\(m-3)(m+2)>0" alt="log_{\frac{1}{2} }^{2}(3x+1)=m\\\\m^{2}-m-6>0\\\\(m-3)(m+2)>0" align="absmiddle" class="latex-formula">
+ - +
__________₀___________₀___________
- 2 3
//////////////////// ///////////////////////
4\\\\3x>3\\\\x>1\\\\log_{\frac{1}{2} }(3x+1)>3\\\\3x+1<\frac{1}{8} \\\\3x<-\frac{7}{8} \\\\x<-\frac{7}{24}" alt="log_{\frac{1}{2} }(3x+1)<-2\\\\3x+1>4\\\\3x>3\\\\x>1\\\\log_{\frac{1}{2} }(3x+1)>3\\\\3x+1<\frac{1}{8} \\\\3x<-\frac{7}{8} \\\\x<-\frac{7}{24}" align="absmiddle" class="latex-formula">
Ответ : (- 1/3 ; - 7/24) ∪ (1 ; + ∞)